In Situ Hybridization, with or Without Tyramide Signal Amplification, in Evaluation of Human Papillomavirus Status In early Stage Cervical Carcinoma - Kubelka-Sabit, Katerina; Prodanova, Irina; Zografski, George; Basheska, Neli (Walter de Gruyter GmbH, 2008)
Conventional in situ hybridization (CISH) can be used for detection of human papillomavirus (HPV) DNA, enabling preservation of the tissue morphology and assessment of the physical state of viral DNA, but has low sensitivity. This study compared the sensitivity and efficiency of in situ hybridization with tyramide signal amplification (ISH TSA) with those of CISH. The HPV status of 77 cases with early stage cervical carcinoma was evaluated with CISH, using biotinylated probes for HPV types 6/11, 16/18 and 31/33/51, and with ISH TSA using probes for HPV types 6/11, 16/18 and 31/33 or 31/33/51. The HPV DNA was detected in 26 (33.8%) cases using CISH, and in 45 (58.4%) cases using ISH TSA. By adding the TSA step, the sensitivity of CISH was enhanced by 24.7%, thus enabling detection of 20 new HPV-positive cases. Multiple HPV infections were detected in four cases. A dot signal pattern was present in 68.9% (31/45) and more than five positive nuclei per sample were found in 82.2% (37/45) of the cases. We found that the ISH TSA system is a fast and simple method for detection of HPV DNA in cervical carcinoma compared to CISH, and is more sensitive and efficient in the detection and typing of HPV, assessment of HPV DNA physical state and evaluation of the number of positive cells than CISH.
Keywords: Cervical carcinoma; Human papillomavirus (HPV); In situ hybridization (ISH); Tyramide signal amplification (TSA)